Fungi and bacteria in the biodeterioration of archeological fibers: analysis using different microscopic techniques - Guiamet, Patricia Sandra (2014)
Pre and post-Columbian archeological textiles from the Southern Andean area, sheltered in Deposit 25 at La Plata Museum (Fig. 1), were analyzed by Olympus BX51optical microscopy (OM), FEI Quanta 200 scanning electron microscopy (SEM) and Leica SP5 confocal laser scanning microscopy (CLSM) with the aim of studying their biodeterioration3 . For over 120 years, these textiles have provided information to archeologists around the world, and it was through the study of many pieces that we now know in detail the characteristics of the material culture of the various groups that inhabited the territory during the national Holocene period.